A Doomsday Reader : Prophets, Predictors, and Hucksters of Salvation. - Daniels, Ted (NYU Press, 1999)
The approach of the year 2000 has made the study of apocalyptic movements trendy. But groups anticipating the end of the world will continue to predict Armageddon even after the calendar clicks to triple 0s. A Doomsday Reader brings together pronouncements, edicts, and scriptures written by prominent apocalyptic movements from a wide range of traditions and ideologies to offer an exceptional look into their belief systems. Focused on attaining paradise, millenarianism often anticipates great, cosmic change. While most think of religious belief as motivating such fervor, Daniels' comparative ap.